THE IMPLEMENTATION OF GREEN ENERGY POLICY IN THE NORDIC COUNTRIES IN TERM OF ENERGY SECURITY: POLITICAL AND REGIONAL COOPERATION APPROACHES - Helmy Ariansyah (International Conference on Social and Islamic Studies, 2021)
This study aims to analyze the political strategies and policies implemented by Nordiccountries, both nationally and in the context of regional cooperation, in addressing to issue ofenergy security through the transition to green energy actions. Government of Nordic countrieshave succeeded in demonstrating a model of green energy policy at national and regional levelsthat is considered effective by many European countries without having a significant burdenon their economic activities. Therefore, it is not surprising that many countries have followedthe steps taken by Nordic governments, especially through accommodative policies andregional cooperation by promoting open energy markets. Through correlative quantitativeresearch method, it can be shown that regional open market on energy supply and economicincentives for the development of renewable energy are key policies on achieving sustainabilityin green energy production in the Nordic region. While using qualitative methods, this studydemonstrates the effectiveness of political actions and regional cooperation in energy sector asthe most effective strategy in achieving energy security, which many other regions in the worldare trying to follow.